Quantifying Topographic Influence on Irradiance Transfer in Permanently Shadowed Regions - P. Mahanti; M. Robinson (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In permanently shadowed regions (PSRs), the surface temperature is influenced by secondary illumination, which changes daily and seasonally due to the sunlight reflected by the surrounding terrain. Understanding how topography affects the transfer of radiant energy can help us quickly interpret the thermal behavior using available topographic data. The amount of radiant energy transferred from a sunlit lunar surface to a PSR depends on the distance and orientation of the sunlit surface to the PSR, and is represented by view factors. In this study, we introduce an approach to systematically represent the combined effects of multiple surfaces using statistical analysis applied to view factor maps. We demonstrate that our proposed approach can explain the contrasting temperatures of two PSRs at the lunar south pole. We verify our theoretical findings using PSR images acquired by the ShadowCam instrument aboard the Danuri lunar orbiter.